Ethnobotanical survey of herbal medicines for anti-COVID-19 used by traditional Chinese medicine pharmacies in Taiwan - Chi, Min-Han; Ko, Chien-Yu; Chi, Ting-Wei; Huang, Chi-Ruei; Lin, Jaung-Geng; Chao, Jung; Huang, Shyh-Shyun (Frontiers in Pharmacology, 2025)
IntroductionTraditional Chinese medicine (TCM) pharmacies in Taiwan have been a vital healthcare resource in Chinese communities, with generations of accumulated TCM knowledge playing a crucial role in infectious disease prevention and treatment. However, as proprietors age and the industry declines, this valuable ethnomedicinal knowledge faces the risk of being lost. Therefore, documenting and analyzing the knowledge used by Taiwanese TCM pharmacies in combating COVID-19 is essential for the preservation and application of ethnomedicine.MethodsThis study employed a stratified sampling method to survey 106 TCM pharmacies in Taiwan, collecting 61 TCM formulae against COVID-19. The medicinal materials were compiled, and analysis were conducted using relative frequency of citation (RFC) and the Phi correlation coefficient to examine the relationships among TCMs. Furthermore, cluster analysis was applied to establish TCM combination patterns.ResultsThis study recorded a total of 70 medicinal materials and identified 30 commonly used ones, categorizing them into four major groups: Group A (heat-clearing and detoxifying): As similar as NRICM101, suitable for moderate to severe cases. Group B (heat-clearing and tonifying): Suitable for mild cases, with both antiviral and immune-boosting effects. Group C (symptom relief): Primarily used for relieving cough, expelling phlegm, and alleviating discomfort. Group D (tonifying and strengthening): Suitable for uninfected individuals to enhance immunity.DiscussionThis study successfully documented and analyzed the TCM usage patterns of Taiwanese TCM pharmacies in combating COVID-19, revealing their alignment with modern TCM theories. The findings not only contribute to the preservation of ethnobotanical knowledge but also serve as a reference for developing herbal prevention strategies and healthcare products, ensuring that traditional medical wisdom can play a greater role within the modern healthcare system.